Novel Mutation of Gene Observed in Congenital Chloride Diarrhea - Ji Hye Cheon; Na Li Yu; Na Mi Lee (Korean Society of Neonatology, 2023)
Congenital chloride diarrhea (CLD) is a rare autosomal recessive disease caused by mutations in the solute carrier family 26 member 3 (SLC26A3) gene on chromosome 7q31. Affected neonates are vulnerable to dehydration, electrolyte imbalance in the form of hyponatremia, metabolic alkalosis, failure to thrive, or even death if left untreated. Genetic testing for mutations should be considered if the clinical diagnosis remains uncertain because early diagnosis and appropriate management are critical to the disease course in CLD. Several mutations have been reported in Korean patients with CLD, with the most common being the c.2063-1G>T mutation. Here, we report the case of a neonate with prenatally suspected CLD with confirmed novel mutations in the SLC26A3 gene (c.2147C>G; p.Ala716Gly).